2016
DOI: 10.1002/pd.4762
|View full text |Cite
|
Sign up to set email alerts
|

MRI reveals hemodynamic changes with acute maternal hyperoxygenation in human fetuses with and without congenital heart disease

Abstract: Objective We investigated the physiologic impact of acute maternal hyperoxygenation (MH) in human fetuses with and without congenital heart disease (CHD) using fetal cardiac magnetic resonance (CMR) in order to explore the potential therapeutic benefits of chronic MH. Methods We examined 17 normal and 20 late gestation human fetuses with CHD on a 1.5 T CMR system. Flows were measured in major fetal vessels using phase contrast MRI. The T2 of umbilical venous blood was measured using T2 mapping. The measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Further into the future, as we begin to understand the complex fetoplacental interactions in fetuses with CHD, manipulation of the fetal circulation via experimental interventions such as maternal hyperoxygenation may provide a non-invasive means of improving cerebral oxygen and substrate delivery in selected patients 61 . Finally, the use of direct fetal cardiac intervention, currently being explored by a small number of centres for a limited set of indications, 62 may develop a role as our understanding and expertise develop in this area.…”
Section: Opportunities For the Futurementioning
confidence: 99%
“…Further into the future, as we begin to understand the complex fetoplacental interactions in fetuses with CHD, manipulation of the fetal circulation via experimental interventions such as maternal hyperoxygenation may provide a non-invasive means of improving cerebral oxygen and substrate delivery in selected patients 61 . Finally, the use of direct fetal cardiac intervention, currently being explored by a small number of centres for a limited set of indications, 62 may develop a role as our understanding and expertise develop in this area.…”
Section: Opportunities For the Futurementioning
confidence: 99%
“…Previous studies of through‐plane single‐vessel fetal phase contrast MRI have relied on Cartesian measurements in target vessels 1,2,10,24 . Using such techniques, flows in the major fetal vessels have been quantified in healthy pregnancies and those affected by growth restriction or CHD 1,24–28 . Further studies have also compared Doppler ultrasound gating and MOG for fetal phase contrast MRI 29 .…”
Section: Discussionmentioning
confidence: 99%
“…At present, MRI is widely used to diagnose human diseases and has become more effective than CT and X-rays for the early diagnosis of human tumors, heart diseases and cerebrovascular diseases [11]. Cheng et al [30] reported that comprehensive motion-compensated highly accelerated 4D flow MRI with ferumoxytol enhancement may be used to improve diagnoses of pediatric congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…The safety and imaging quality of MRI has been confirmed in pediatric and adult patients with congenital heart disease and pacemakers [10]. Porayette et al [11] reported that MRI effectively identified hemodynamic changes with acute maternal hyperoxygenation in human fetuses with and without congenital heart disease. In clinics, left ventricular eccentricity index measured by cardiac MRI has been used to assess right ventricular hemodynamics and myocardial fibrosis in congenital heart disease, suggesting that MRI is a more effective diagnostic method for congenital heart disease compared to computed tomography (CT) and ultrasonography [12].…”
Section: Introductionmentioning
confidence: 99%